The Impact of Large-scale Social Restrictions on the Incidence of COVID-19: A Case Study of Four Provinces in Indonesia - Suraya, Izza; Nurmansyah, Mochamad Iqbal; Rachmawati, Emma; Al Aufa, Badra; Koire, Ibrahim Isa (UI Scholars Hub, 2020)
The Indonesian government has chosen to implement large-scale social restrictions (Pembatasan Sosial Berskala Besar/PSBB) to minimize the spread of COVID-19. Large-scale social restrictions is a government policy aimed at restricting the internal movement of people in a bid to reduce the spreading of SARS-CoV-2. This study aims at assessing the impact of large-scale social restriction measures on the incidence of COVID-19 cases in the four provinces of Indonesia. Time series analysis was used to describe the trends of COVID-19 case by using surveillance data from the Ministry of Health of Indonesia. Quasi- Poisson regression with an interaction model was used to estimate the incidence rate ratio (IRR). IRR was calculated to compare an incidence rate before and during PSBB implementation. The trend of COVID-19 cases in the provinces of West Java, East Java, Banten, and Jakarta continued to fluctuate. These four provinces continue to experience a significant increase in COVID-19 incidence rate ratio after the first and second PSBB period implementation compared to the time of before PSBB implementation. Lack of proper implementation of the large-scale social restriction led to the PSBB’s ineffectiveness in reducing the number of COVID19 cases in each of the provinces.